2016
DOI: 10.1161/strokeaha.115.011453
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Course of Dynamic Cerebral Autoregulation in Patients With Intracerebral Hemorrhage

Abstract: Reports of dCA in patients with ICH group are scarce, yet diverse. In a case-control study, a higher gain was observed within 3 days of ICH onset when compared with the healthy controls, indicating a less effective dCA during the acute stage. 7 In a recent study, researchers obtained serial measurements and stated that a higher bilateral gain could last 5 days Background and Purpose-Cerebral autoregulation is crucial in patients with intracerebral hemorrhage. Dynamic cerebral autoregulation is probably altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 32 publications
2
113
1
3
Order By: Relevance
“…Four studies detailed end‐tidal carbon dioxide (EtCO 2 ) values for acute ICH patients. These ranged from 34.3 to 34.9 mm Hg in the acute phase (<72 hours) and 34.7 to 35.2 mmHg in the chronic (>72 hours) phase . Studies provided varying detail for BP recordings, with three providing no data, three providing mean arterial pressure (MAP), and one providing systolic readings only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies detailed end‐tidal carbon dioxide (EtCO 2 ) values for acute ICH patients. These ranged from 34.3 to 34.9 mm Hg in the acute phase (<72 hours) and 34.7 to 35.2 mmHg in the chronic (>72 hours) phase . Studies provided varying detail for BP recordings, with three providing no data, three providing mean arterial pressure (MAP), and one providing systolic readings only.…”
Section: Resultsmentioning
confidence: 99%
“…All eight studies assessed cerebral hemodynamic measurements at rest. In one study, providing CBV data up to 30 days following ICH onset, it was reported that CBV in both the affected and unaffected hemispheres failed to return to control subject values at all assessed time‐points until Day 30 …”
Section: Resultsmentioning
confidence: 99%
“…Haematoma expansion may be attenuated by acute blood pressure reduction, but concern persists that dynamic CA may be impaired after ICH, making perfusion of the brain passively dependent on blood pressure 6. Perihaematoma tissue is moderately hypoperfused and therefore may be vulnerable to blood pressure reduction.…”
Section: Clinical Applications Of Ca Studies In Strokementioning
confidence: 99%
“…Várias patologias de incidência significativa e impacto considerável na qualidade de vida, tais como insuficiência cardíaca, AVCi, traumatismo craniano, doença arterial carotídea e hemorragia cerebral envolvem alterações do FSC e dos seus mecanismos regulatórios 18,20,22,[70][71][72] . A melhor compreensão dos determinantes do FSC humano é um grande desafio, em especial pela dificuldade de realizar medições intracraniana.…”
Section: Complexidade Da Hemodinâmica Cerebral Humanaunclassified
“…A perfusão cerebral humana é extremamente sensível às alterações da Este modelo de análise da AR utilizando flutuações espontâneas da PA tem sido aplicado em diferentes condições na prática clínica como, insuficiência cardíaca, doença da artéria carotídea, trauma craniano encefálico, diabetes, doenças gestacionais, AVCi e em situações clínicas de utilização de dispositivos de assistência circulatória 18,20,21,70,71,144,145 .…”
Section: Mecanismo Metabólicounclassified